If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 3x = 3 + -1(x + 1) Reorder the terms: 14 + 3x = 3 + -1(1 + x) 14 + 3x = 3 + (1 * -1 + x * -1) 14 + 3x = 3 + (-1 + -1x) Combine like terms: 3 + -1 = 2 14 + 3x = 2 + -1x Solving 14 + 3x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 14 + 3x + x = 2 + -1x + x Combine like terms: 3x + x = 4x 14 + 4x = 2 + -1x + x Combine like terms: -1x + x = 0 14 + 4x = 2 + 0 14 + 4x = 2 Add '-14' to each side of the equation. 14 + -14 + 4x = 2 + -14 Combine like terms: 14 + -14 = 0 0 + 4x = 2 + -14 4x = 2 + -14 Combine like terms: 2 + -14 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| f(x)=3x^2+2x+3 | | 1.5*12=18 | | 44=5x+24 | | 285=60x-20 | | F/8=32 | | 26x+15x=-8x^2 | | (7-y)(3y+8)=0 | | 5-2x=5x-3 | | (n+4)-10=2 | | 44=(4x+6) | | 2g-3=q | | 8x-8y=-61 | | 8x-8y=-6 | | 6ln(2x)=54 | | (2x-61)+(x-17)+3x=360 | | 4h-8h=h | | U/5=15 | | 7+6n=47 | | (-10-6)+8+9= | | 4x-4y=-6 | | 7/4x-2=-1/2x-2/3 | | 19x-17(14x+11)= | | 0.2=(x/x=11.1) | | x-5+x+.75x+.05x+3=360 | | 4/9u=8 | | (5x)5=6 | | y=x^2-10+24 | | 3/4(0.7c)=42 | | 3x-3=x-6 | | 4x+5y=208 | | 2(-10+7x)=-118 | | (12x^7-27x^5)/3x^3 |